EFL PRE-SERVICE TEACHERS PERCEPTION OF TECHNOLOGY INTEGRATION IN ENGLISH LANGUAGE INSTRUCTION - Nayla Ridha; Rahmah Fithriani (Universitas Indraprasta PGRI, 2023)
Technological developments brings a good effect on English education. Several studies have shown that the use of technology is very helpful for teachers in the process of teaching English. However, the facts on the field state that many obstacles that made it difficult for teachers to apply technology in their teaching. On this basis, researchers aimed to examined the perceptions of EFL pre-service teachers regarding the use of technology in English instruction during teaching practicums in a junior high school in Medan, Indonesia. This study employs a qualitative research method. Participant observations and interviews were used to obtain data from six pre-service teachers. The results show that the pre-service teachers frequently utilize laptops, projectors, and smartphones to access websites and applications for English instruction. This study also asserts that employing technology during English instruction has numerous advantages, such as enhancing student motivation and collaboration, and increasing pre-service teachers' creativity and technology skills. Furthermore, some challenges in integrating technology into instructional practices were also acknowledged, which include being time-consuming., lacking of facility, and making the classroom less conducive